The Determinants of Survival among African Manufacturing Firms. - Söderbom, M; Teal, F; Harding, A (2006)
Recent reforms in many African economies of their trading and exchange rate regimes have eliminated much of the protection that previously limited competition. Despite these reforms, African manufacturing firms remain unsuccessful, particularly in international export markets. In this article we focus on the role of total factor productivity (TFP) in determining whether or not firms can survive in the subsequent period. We use a pooled panel data set of firms in Ghana, Kenya, and Tanzania that spans a period of 5 years. We find that productivity influences subsequent firm survival among large, but not small, firms. We investigate whether this result can be explained by differences in risk or the persistence of TFP. We find no evidence that this is the case. The result may be driven by covariance between the unobserved outside option and the value in remaining in existence that makes optimal exiting for small firms largely independent of productivity in the previous period.